(untitled) (Global Journal of Human-Social Science, 2015)
Reading centers are an important and active part of most elementary classrooms. As a teacher of young children in Saudi Arabia, I observed that there were times when students did not benefit from their literacy experiences, and at other times there was a good deal of activity around their experiences in the reading centers I had developed for them. As a result of this experience in my own classroom, I have continued to have great interest in the role of reading centers for young children’s learning. This study is focused on the literacy activities in the reading centers in the elementary classroom. Specifically it is focused on exploring the differences between boys and girls as they participate in reading centers in their classroom. There are differences between boys’ and girls’ reading interests that have been documented in the research. This study seeks to examine these differences in one elementary second grade classroom.